Developing scaffolded virtual learning environments for people with autism - Kerr, Steven John (2005)
Virtual Environments offer the potential for users to explore social situations and experience different behaviour responses for a variety of simulated social interactions. One of the challenges for the VE developer is how to construct the VE to allow freedom of exploration and flexibility in interactive behaviour, without the risk of users deliberately or inadvertently missing important learning goals. The program has to be structured to guide the user in their learning and to take into account different levels of ability. This embedded ‘scaffolding’ within the VE software can aid the user’s learning in different contexts, such as individual, tutored or group learning situations.